Reproductive features of the swimming crab Callinectes danae(Crustacea, Portunoidea) on the subtropical coast of Brazil: a sampling outside the estuary - Andrade,LS (2015)
AbstractThe life cycle of the crab Callinectes danae is estuarine-dependent, and studies on aspects of their biology should also cover marine areas. The present study investigated the sexual maturity, as well as habitat preference by adults in different gonadal stages, and the crabs’ reproductive periodicity outside the estuary. Three bays on the subtropical southeastern coast of Brazil were sampled monthly for two years. For each bay, six transects were established, four of them parallel to the beach line (5, 10, 15 and 20 m depth), as well as one transect in an exposed area, and another sheltered from the action of waves. The results showed that the pattern of spatio-temporal distribution of adults C. danae was similar in three bays, although the highest abundance was found in Ubatumirim. Females with developed gonads/ovigerous females were found in greater abundance than females with rudimentary/developing gonads, mainly in deeper transects. Although the areas sampled have different environmental characteristics, the reproductive pattern of the species did not change, showing continuous reproduction throughout, with more abundance of reproductive females on spring and summer. Males reached maturity at larger sizes than females in all three bays.